MAMBANGUN KEPEMIMPINAN YANG EFEKTIF UNTUK MERAIH KEUNGGULAN KOMPETITIF ORGANISASI - Siti Nurhayati (Jurnal Ekonomi Dan Bisnis, 2015)
Recently, the business develop very rapidly that caused of the trade become to free system. The consequence is the business organization must compete with other. To reaches  the success of their business, each organization must have the effectiveness system of leadership. The  effectiveness system of leadership has some characteristic such :a. they have a high intelligenceb. have the social maturity and breadthc. have an inner motivation and achievement drivesd. have the human relation attitudes                Implementing the effectiveness system of leadership also means that the leader can empowering people to become high performance (excellence) with their competence and capability. High performance (excellence) of employers is “the streght” of an organization that may developed as an competitive advantage. Keywords : competitive advantage, leadership, empowerment.